The difficulty of establishing the diagnosis of pediatric COVID-19 in Indonesia - Kurniawan Taufiq Kadafi (Pediatric Sciences Journal, 2022)
The Covid-19 pandemic has not shown any signs of ending soon. Until May 1, 2020, the latest data recorded that Covid-19 cases in the world have reached 3,336,680 cases, with 235,245 people died and 1,054,786 people recovered. Of Â the number of still-active cases, 98% are mild cases, while the remaining 2% are severe. Since it was first identified (December 2019) until it was announced as a pandemic on March 11, 2020), cases of children have not escaped the effects of infection.